Preparation of folic acid-chitosan complex (eco-yellow) and its application for adsorption of mutagens and carcinogens - Jeon, H.-K.; Kim, Y.-J.; Ryu, J.-C. (2009)
Folic acid, a pteridine derivative, is abundant in liver and green plants and is a growth factor for some bacteria. Chitosan is a unique polysaccharide derived from chitin and is utilized as adsorbents of organic trace pollutants in environmental water sample. In this study, we have found that chitosan was suitable as a solid support to carry folic acid. And it was examined that folic acid could form an insoluble material when mixed with chitosan, a polyglucosamine, and the solid chitosan-folic acid complex (eco-yellow) thus prepared could efficiently trap polycyclic mutagenic compounds. The adsorption of the test compounds was observed using UV/Visible spectrometry. The order of extent of removal by eco-yellow was B[a]P (62. 0%)>2-AA (56. 2%)>QC (55. 9%)>Trp-p-2 (40. 2%). From these results, eco-yellow may be expected as a useful adsorber for several polycyclic mutagens and carcinogens. ？ 2009 The Korean Society of Environmental Risk Assessment and Health Science and Springer.